Sodium butyrate has anti-proliferative, pro-differentiating, and immunomodulatory effects in osteosarcoma cells and counteracts the TNFα-induced low-grade inflammation. (16th January 2018) - Perego, Silvia; Sansoni, Veronica; Banfi, Giuseppe; Lombardi, Giovanni
Butyrate, an essential factor for colonocytes and regulator in the development of colon cancer, is partially absorbed by the gut. It influences the proliferation and differentiation of several cell types including osteoblasts. We evaluated the effects of different doses of butyrate on differentiation and functionality of osteosarcoma cells in vitro and the expression of a pro-inflammatory phenotype in a normal or inflammatory environment. SaOS-2 osteosarcoma cells were induced to differentiate and contemporarily treated for 24 h, 48 h, or 7 days with sodium butyrate 10 −4, 5 × 10 −4, or 10 −3  M in the presence or absence of tumor necrosis factor alpha (TNFα) 1 ng/mL, a pro-inflammatory stimulus. Despite the mild effects on proliferation and alkaline phosphatase activity, butyrate dose- and time-dependently induced the expression of a differentiated phenotype (RUNX2, COL1A1 gene expression, and osteopontin gene and protein expression). This was associated with a partial inhibition of nuclear factor kappa B (NF-κB) activation and the induction of histone deacetylase 1 expression. The net effect was the expression of an anti-inflammatory phenotype and the increase in the osteoprotegerin-to-receptor activator of nuclear factor kappa-B ligand (RANKL) ratio. Moreover, butyrate, especially at the highest dose, counteracted the effects of the pro-inflammatory stimulus of TNFα 1 ng/mL. Butyrate affects osteosarcoma cell metabolism by anticipating the expression of a differentiated phenotype and by inducing the expression of anti-inflammatory mediators.